The Effect of Liquidity, Leverage and Firm Size on Financial Distress - Mohamad Zulman Hakim; Dewi Anggraeni; Budi Rohmansyah; Seleman Hardi Yahawi; Indra Gunawan Siregar; Eko Sudarmanto (Cita konsultindo, 2022)
Intense economic competition can place companies in a state of prolonged and increasingly out of control financial crisis. so that it will result in the company being in a financial condition that experienced a decline before bankruptcy or what is commonly known as Financial Distress. Researchers discuss the effect of liquidity, leverage and company size on Financial Distress in this article. The technique used in this study was purposive sampling with a sample of 19 companies. This research data was obtained from the Property and Real Estate sectors through the Indonesia Stock Exchange for the 2019-2021 period. The findings in this study reveal that firm size has an effect on Financial Distress and liquidity and leverage have no effect on Financial Distress.